A journey to the centre of the Earth - Verne, Jules, 1828-1905 (Classics illustrated (Newbury (England)), 2016)
Presents a graphic novel retelling of the classic text featuring Professor Lidenbrock and his nephew Axel who travel across Iceland, and then down through an extinct crater towards a sunless sea where they enter a living past and are confronted with the origins of man. Includes information on the author, discussion topics, and a timeline.